Case study on supply and demand for parking facilities at LYC Hypermarket (road Gambang-Kuantan) - Nurshahira Saidatul Hasna , Abdul Jabar (2015)
The parking facilities is an important element in providing good transportation planning policy at a certain area. The increase of demand for parking space especially at shopping area requires ample, comfortable and safe parking space which taken into consideration the potential space and the use of ground especially at crowded area. The objective of this research is to assess the demand parking space available at LYC hypermarket, to assess the parking parameter such as duration, occupancy and turnover of parking and to recommend the improvement of parking facilities at LYC hypermarket. The research area is located in road Gambang-Kuantan. The finding from thus research through observation of entering and leaving vehicle method, it is clearly shows that the number of parking space at the LYC hypermarket, Kuantan is sufficient to cater the needs even high demand of consumers especially during peak hours . However, the parking facilities provided does not fulfilled the standard quality of a parking lots and there is no specific entrance and exit to the hypermarket. In preparing the planning of a parking facilities, the organization involved should take into consideration a few important criteria and it has to be planned well as to enable the facilities provided can cater for the increments of the number of vehicles from time to time.